"Mountain of destiny" : Nanga Parbat and its path into the German imagination - Höbusch, Harald (Studies in German literature, linguistics, and culture, 2016)
"Never has a mountain occupied the German imagination longer and more thoroughly than Nanga Parbat, the world's ninth-highest peak, located in present-day Pakistan. Repeatedly referred to in the 1930s as the German "mountain of destiny," over a period of roughly two decades from 1932 to 1953 it became not only the destination of six German mountaineering expeditions, but also the quintessential German "mountain of the mind" onto whose slopes German mountaineers, mountaineering officials, politicians, writers, and filmmakers projected some of the most pressing social, political, and cultural concerns of their times. This book is a detailed study of that process"...